Sistem Pendukung Keputusan Untuk Penentuan Mahasiswa Berprestasi Universitas Baturaja Menggunakan Metode AHP dan TOPSIS - Desti Arini (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2024)
Determining outstanding students at Baturaja University is an important process that requires fair and objective assessment based on relevant criteria. The purpose of this study is to develop a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methods to assist the university team in the process of selecting outstanding students. This study took a sample of 50 students who had a Cumulative Grade Point Average (GPA) ≥ 3.5 and a track record of non-academic achievements. The four main criteria used in the assessment are Academic, Non-Academic, Attendance, and Attitude and Ethics. AHP is used to determine the weight of each criterion, while TOPSIS is applied to obtain the final ranking of students based on their proximity to positive and negative ideal solutions. The expected results of this study are a DSS that is able to provide objective student ranking recommendations, reduce subjectivity in assessment, and assist the selection committee in making fairer and more consistent decisions. This DSS is expected to improve efficiency and accuracy in the process of selecting outstanding students at Baturaja University.